PENDEKATAN STORYTELLING INTERAKTIF SEBAGAI STRATEGI EDUKATIF DALAM PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA SEKOLAH DASAR DI RUANG PUBLIK MASJID AGUNG ATS-TSAUROH KOTA SERANG - Rindu Sastri, Widya; Siregar, Herlina; Fatimah, Nining (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This activity aims to provide education on self-protection from sexual violence to elementary school-aged children through an interactive storytelling approach in the public space of the Ats-Tsauroh Mosque in Serang City. The background to this activity is based on children's low understanding of their private bodies and limited sexual literacy due to a lack of education appropriate to children's developmental characteristics. The activity was carried out directly in the public space of the Ats-Tsauroh Mosque in Serang City, involving elementary school-aged children and their accompanying parents. Education was delivered through interactive storytelling combined with discussions, questions and answers, and simple educational games to increase participant engagement. The results of the activity showed that children had a better understanding of self-protection concepts, such as recognizing private body parts, understanding their boundaries, and knowing how to respond to unsafe situations. Furthermore, conducting the activity in a public space created a more open atmosphere and encouraged active participant participation. Therefore, the interactive storytelling approach in community service activities in public spaces can be an effective educational strategy in increasing children's understanding of self-protection from sexual violence.